The Analysis of Teachers’ Active Role in Increasing Student Learning Motivation - Widarbowo, Dodik (Mudir : Jurnal Manajemen Pendidikan, 2023)
In this study, qualitative research was the chosen research approach. In this study, documentation, interviews, and observations were used as data collection methods. Through observation and data triangulation, the validity of the data is checked. Techniques for data analysis were applied in stages, beginning with reduction, data presentation, and conclusion. The findings of this study suggest that pupils' motivation for learning is at its highest level. This is evident when learning takes place because the teacher can make students excited about the lesson. Therefore, to overcome students who lack interest in subjects, among others, the teacher tells the story of the Prophet so that students feel motivated to learn cultural history, then intersperses it with humor so that students do not feel bored and excited when learning. The teacher also gives appreciation to students when there are students who get the highest scores in the class.